Discrete multivariate associated kernel estimators using two multiplicative bias correction methods. Issue 2 (1st February 2022) - Harfouche, L.; Zougab, N.; Adjabi, S.; Funke, B.
Abstract: Two multiplicative bias correction (MBC) approaches for nonparametric multivariate associated kernel estimators for joint probability mass functions in the context of discrete supported data are proposed. Both techniques reach an optimal rate of convergence of the mean integrated squared error. We show some properties of the MBC multivariate associated kernel estimators like bias, variance and mean integrated square error. A simulation study and an application on a real count data set illustrate the performance of the MBC estimators based on the Dirac Discrete Uniform associated kernel in terms of the integrated squared error and integrated squared bias.